2020
DOI: 10.1364/oe.410429
|View full text |Cite
|
Sign up to set email alerts
|

Phase-only modulation with two vertical aligned liquid crystal devices

Abstract: Spatial Light Modulators (SLMs) are widely used in several fields of optics such as adaptive optics. SLMs based on Liquid Crystal (LC) devices allow a dynamic and easy representation of two-dimensional phase maps. A drawback of these devices is their elevated cost, preventing a massive use of the technology. We present a more affordable approach based on the serial arrangement of vertical aligned LC devices, with characteristics of phase modulation similar to a widely used parallel aligned LC device. We discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The DPM of these VA-LCoS devices is dependent on the display’s temperature; thermoelectric modules were used to maximize the DPM at values slightly larger than π. The phase modulation properties of these devices present temporal fluctuations (or flickering) at high frequencies, 12 although these are negligible for visual applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DPM of these VA-LCoS devices is dependent on the display’s temperature; thermoelectric modules were used to maximize the DPM at values slightly larger than π. The phase modulation properties of these devices present temporal fluctuations (or flickering) at high frequencies, 12 although these are negligible for visual applications.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we examined the modulation properties of VA-LCoS; it was shown that using two VA-LCoS arranged in series or in a double pass through one of these (thus allowing phase summation) produced phase modulation outcomes similar to those of PA-LCoS, but with a significantly lower cost (at least an order of magnitude less) and improved compactness. 12 In this context, we demonstrate here the potential of this phase-modulation approach consisting of two VA-LCoS devices for the simulation and correction of high-order aberrations (HOAs) in the human eye. We perform visual acuity (VA) and contrast sensitivity (CS) tests in a group of subjects, with their eye's aberrations either corrected or induced with amounts similar to that in severe keratoconus [root-mean-square (RMS) error ¼ 1 μm for 5-mm-diameter pupil].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…VA-LCoS are typically used as high-contrast amplitude modulators [3], not holding a large depth of phase modulation, barely surpassing π radians. In a recent study it was shown how the use of two VA-LCoS arranged in series (thus allowing phase summation) could develop phase modulation outcomes very similar to those of the gold standard PA-LCoS, with a significant lower cost and improved compactness [4].…”
Section: Introductionmentioning
confidence: 99%